The accurate calculation of resonances in multiple-well oscillators - Fernández, Francisco Marcelo (2008)
Quantum–mechanical multiple-well oscillators exhibit curious complex eigenvalues that resemble resonances in models with continuum spectra. We discuss a method for the accurate calculation of their real and imaginary parts.